Harnessing IoT for Industrial Efficiency: Innovations in Automation and Process Optimization - Aripin, Zaenal (KRIEZ ACADEMY : Journal of development and community service, 2024)
The Internet of Things (IoT) has become a transformative force in industrial automation, offering significant enhancements in efficiency, cost-effectiveness, and real-time decision-making. This study provides a comprehensive examination of IoT’s application in industrial settings, with a focus on its impact on predictive maintenance, real-time monitoring, supply chain management, quality assurance, and energy optimization. Using a mixed-method approach, the research integrates qualitative insights from case studies and interviews with quantitative data from industry surveys in Indonesia. The results reveal substantial improvements in operational performance, cost reduction, and workplace safety across various sectors. However, significant implementation challenges persist, including cybersecurity vulnerabilities, high initial investments, and interoperability issues. The findings underscore the critical need for strategic planning, standardization, and robust cybersecurity frameworks to fully leverage IoT’s potential in industrial environments.